Does Duration of Pain at Baseline Influence Clinical Outcomes of Low Back Pain Patients Managed on an Evidence-based Pathway?. Issue 17 (1st September 2018) - Jess, Mary-Anne; Ryan, Cormac; Hamilton, Sharon; Wellburn, Shaun; Atkinson, Greg; Greenough, Charles; Coxon, Andrew; Ferguson, Diarmaid; Fatoye, Francis; Dickson, John; Jones, Andrea; Martin, Denis
Abstract : Study Design: Longitudinal observational study. Objective: To investigate the association between the duration of pain at baseline and the clinical outcomes of patients with low back pain (LBP) enrolled on the North East of England Regional Back Pain and Radicular Pain Pathway (NERBPP). Summary of Background Data: The NERBPP is a clinical pathway based upon National Institute for Health and Care Excellence (NICE) guidelines (2009) for LBP of <1-year duration. Recent changes to NICE guidelines (2016) advocate the same management for all LBP patients regardless of pain duration. Methods: Patients with LBP referred onto the NERBPP by their General Practitioner between May 2015 and January 2017 were included. Data from 667 patients, who provided pre- and post data for pain (Numerical rating scale), function (Oswestry Disability Index), quality-of-life (EuroQol five-dimension, five-level questionnaire), anxiety (the Generalized Anxiety Disorder Screener), and depression (the Patient Health Questionnaire), were analyzed using a series of covariate-adjusted models. Patients were categorized into four groups based upon baseline pain duration: <3 months, ≥3 to <6 months, ≥6 months to <12 months, ≥12 months. Results: Each group showed improved outcomes greater than the minimal clinically important difference (MCID) for each measure as defined in NICE guidelines (2016). There was a trend toward better outcomes for those with shorter pain durations. The magnitude of the differences between the groups, in most instances, was below the MCID. For example, mean improvement in function for those with baseline pain duration <3 months was 20 points and 12 points for those of pain duration ≥12 months, both above the MCID of ≥10. Conclusion: Patients with different durations of LBP at baseline improved on the NERBPP, supporting the recent modification to NICE guidelines. However, those with shorter durations of pain may have superior outcomes in the short term, suggesting added benefit in getting patients onto the pathway in the early stages of LBP. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text